2011
DOI: 10.1073/pnas.1113486108
|View full text |Cite
|
Sign up to set email alerts
|

Repressor element 1 silencing transcription factor (REST) controls radial migration and temporal neuronal specification during neocortical development

Abstract: Neurogenesis requires mechanisms that coordinate early cell-fate decisions, migration, and terminal differentiation. Here, we show that the transcriptional repressor, repressor element 1 silencing transcription factor (REST), regulates radial migration and the timing of neural progenitor differentiation during neocortical development, and that the regulation is contingent upon differential REST levels. Specifically, a sustained presence of REST blocks migration and greatly delays-but does not prevent-neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 30 publications
5
67
0
Order By: Relevance
“…Predictably, REST is downregulated during neurogenesis, at both the mRNA and protein levels, to allow these genes to be expressed (Ballas et al, 2005;Guardavaccaro et al, 2008;Westbrook et al, 2008;Gao et al, 2011). Forced expression of REST during neurogenesis results in defects in cortical migration and axonal pathfinding (Paquette et al, 2000;Mandel et al, 2011). Consistent with these observations, Rest promoter activity is itself repressed in some postmitotic cortical neurons (Ballas et al, 2005).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Predictably, REST is downregulated during neurogenesis, at both the mRNA and protein levels, to allow these genes to be expressed (Ballas et al, 2005;Guardavaccaro et al, 2008;Westbrook et al, 2008;Gao et al, 2011). Forced expression of REST during neurogenesis results in defects in cortical migration and axonal pathfinding (Paquette et al, 2000;Mandel et al, 2011). Consistent with these observations, Rest promoter activity is itself repressed in some postmitotic cortical neurons (Ballas et al, 2005).…”
Section: Introductionsupporting
confidence: 69%
“…For example, in adult mouse hippocampus, Rest transcripts are upregulated in response to ischemic insult (Kokaia et al, 1994) and are proposed to contribute to cell death through regulation of glutamate excitotoxicity (Calderone et al, 2003). Rest mRNA levels and RE1 occupancy of REST target genes also increase in peripheral neurons in response to nociceptive stimuli (Michaelevski et al, 2010;Uchida et al, 2010;Ben-Yaakov et al, 2012) and have been associated with epilepsy (McClelland et al, 2011;Pozzi et al, 2013). Mechanisms that regulate Rest mRNA levels in these different functional contexts are unknown, but an early study (Kojima et al, 2001) reported that cell type-specific expression of REST was not strictly promoter-dependent, and our studies herein support the suggestion of post-transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Both mutant ERK phenotypes would be predicted by stabilization of REST through loss of ERK1/2 phosphorylation of S861/864. A similar differentiationarrested phenotype was also observed after persistent expression of REST in neural progenitors in vivo (26). REST expression has been reported in adult brain (27,28) as well as in neural progenitors during neurogenesis.…”
Section: Discussionsupporting
confidence: 52%
“…As neural progenitors differentiate into neurons, REST and its corepressors depart the RE1 site of selected neuronal genes, triggering transcriptional activation. In newborn neurons, the level of expression of REST targets is adjusted further by CoREST-MeCP2 repressor complexes, which remain bound after REST (8,49). A recent study suggests that MeCP2 localizes to nearly every nucleosome and, as such, may not bind preferentially to individual genes (50).…”
Section: Discussionmentioning
confidence: 99%